The Role of Islamic Education in Forming a Sakinah Family in Sambalagi Village, Bungku Pesisir District - Muh. Rizal Masdul; Rahmawati; Adriansyah Lasawali; Abdul Mufarik A. Marhum (Universitas Muhammadiyah Palu, 2022)
Islamic education has a vital role in forming a sakinah family because through education, and family members can behave well as required in Islamic teachings. Education provides understanding to husband and wife in carrying out their rights and obligations, giving knowledge to parents in educating their children, interacting islamically and placing islamic teachings in the process of family interaction to create a sakinah family. This is the finding in this study.